Relationships among sport-products self-congruence, product love, product trust, and purchase behavior of sports-for-all club members - Chae-Man Na (Korea Institute of Sport Science, 2020)
Purpose The purpose of this study was to analyze the relationships among sport-products self-congruence, product love, product trust, and purchase behavior of sports-for-all club members through structural equation model analysis. Methods A survey was conducted targetting 227, men & women in their twenties who are members of MTB, Tennis, Badminton, Golf in at the 8 in Seoul metropolitan area. For sampling method, convenience sampling method was used, while the questionnaire was self-administered. In an effort to verify the proposed structural model, this study used IBM SPSSWIN Ver. 21.0 and AMOS 18.0. Results First, actual self-congruence has positive influence on the product love. Second, ideal self-congruence didn't have positive influence on the product love. Third, social self-congruence has positive influence on the product love. Fourth, product love has positive influence on the product trust. Fifth, product trust has positive influence on the positive word-of-mouth. Sixth, product trust has positive influence on the repurchase intention. Seventh, product trust has positive influence on the attitudinal loyalty.